Maximizing the Digital Marketing System Through Micro Business Assistance at the Babakan Ciwaringin Cirebon Islamic Boarding School Cooperative - Manggabarani, Alfatih S.; Saragih, Guntur; Hadi, Prasetyo; M., Faisal (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This activity aims to improve participants’ skills in digital marketing, which is one of the most effective marketing activities, capable of increasing income by up to 70%. The Babakan Ciwaringin Cirebon Islamic Boarding School Cooperative, as a partner in this project, is a micro-enterprise that has been managed traditionally and has been affected by the COVID-19 pandemic. Even though there is a strong desire from management to develop this cooperative so that it can help the MSMEs that collaborate with it, there are a number of challenges that need to be overcome. The Islamic boarding school cooperative wishes to expand its business by developing a refill drinking water business, which previously only met the needs of 7 family cottages. Now wants to develop this business so that it can be marketed for the needs of all cottages in Ciwaringin village and the surrounding community. It is hoped that in the future this business can develop and be able to become a business pioneer to meet the needs of 7 family cottages. The presence of the FEB UPN Veteran Jakarta Abdimas Team is expected to help realize the business This is done in stages through a created website and branding process.